Finite element simulation of electrochemically reversible, quasi-reversible and irreversible linear sweep voltammetry at the wall tube electrode - Klymenko, O; Gavaghan, D; Harriman, K; Compton, R (2002)
A finite element approach for numerical simulation of linear sweep voltammetry at the wall tube electrode is presented. Working curves and surfaces are computed and reported which permit the analysis of reversible, quasi-reversible and irreversible voltammograms for all voltage scan rates. © 2002 Elsevier Science B.V. All rights reserved.